Effect of day 3 embryo morphometrics and morphokinetics on survival and implantation after slow freezing-thawing and after vitrification-warming: a retrospective cohort study - Elia Fernandez Gallardo; Carl Spiessens; Thomas D'Hooghe; Sophie Debrock (BMC, 2017)
Abstract Background Morphometric and morphokinetic evaluation of in vitro cultured human embryos allows evaluation without time restriction and reduces intra- and inter-observer variability. Even though these technologies have been reported to improve the quality of cleavage stage embryo evaluation during fresh culture, possible advantages in the evaluation of cryopreserved embryos have been scarcely explored. This study aims to compare morphometric and morphokinetic parameters between slow frozen and vitrified embryos and to determine their relationship to embryo survival and implantation rate (IR) after thawing/warming. Methods During fresh culture, morphometric characteristics (Total Cell Volume (TCV), symmetry, fragmentation and number of blastomeres) were measured in 286 thawed/warmed embryos. Likewise, after thawing/warming, similar morphometric characteristics were measured in 135 survived embryos. Moreover, morphokinetic parameters (time to mitosis resumption and time to compaction) were measured in 90 embryos after thawing/warming. Then, using linear regression, we investigated the differences between vitrified and slow frozen embryos and the relation of the measured characteristics to embryo survival and IR. Statistical corrections were applied to account for data clustering and for multiple testing. Results Vitrified embryos resume mitosis and start compaction significantly earlier than slow frozen embryos. Mitosis resumption rate was 82% for vitrified and 63% for slow frozen embryos and median time to mitosis resumption was 7.6 h and 13.1 h (p = 0.02), respectively. Compaction rate was 62% in vitrified and only 23% in slow frozen embryos. Median time to compaction was 18.1 h for vitrified embryos but, for slow frozen could not be computed since less than half of the slow frozen embryos reached compaction (p = 0.0001). Moreover, intact embryos resume mitosis significantly earlier than not intact ones regardless of the freezing method (rate: 79% vs. 66%, median time: 7.6 h vs 14.6 h, respectively, p = 0.03). Regarding morphometrics, slow frozen embryos showed lower TCV and higher blastomere symmetry after thawing than vitrified embryos despite having similar blastomere number. IR was related to blastomere number at cryopreservation in slow frozen embryos, but not in vitrified ones. Conclusions Interestingly, vitrified/warmed embryos undergo mitosis resumption and compaction significantly earlier than slow frozen/thawed embryos. However, the clinical use of this morphokinetic parameters still remains to be investigated in larger studies. Trial registration Retrospectively registered on December 15, 2015 NCT02639715 .